PHYTOCHEMICAL ANALYSIS OF BITUNG TREE SEEDS (Baringtonia asiatica L.) - Hendra Pratama Maliangkay; Rolef Rumondor; Mario Walean (Indonesian Biodiversity Journal, 2021)
This study aims to obtain data on the phytochemical content of the methanol extract of Baringtonia asiatica. Obtain data on the phytochemical content of the B. asiatica clorform extract. This research was carried out in the Biology laboratory and Chemistry Laboratory, State University of Manado. The study consisted of extraction and phytochemical analysis using the Harborne method, the results showed that from the extraction process the highest yield was obtained in extracts with n-hexane solvent, then chloroform and methanol. The results of phytochemical analysis show that saponins are the phytochemical group with the strongest intensity found compared to other phytochemical groups. Furthermore, flavonoids were found in high intensity also in the analyzed samples.